Purinergic signaling and cholangiocyte regeneration: a new frontier in ischemic liver injury - Nwaduru, Chinedu; Anyagwa, Onyekachi Emmanuel; Fenlon, Michael; Buff, Michelle; Selim, Motaz; Botha, Jean; Kastenberg, Zachary; Zimmerman, Michael (Frontiers in Transplantation, 2026)
Cholangiocytes—the epithelial cells lining the biliary tree—are especially vulnerable to ischemic injury, particularly in the setting of orthotopic liver transplantation (OLT). This susceptibility stems from their reliance on an arterial blood supply and limited anaerobic capacity, predisposing them to hypoxia-induced damage. While significant research has focused on hepatocellular ischemia-reperfusion injury (IRI), the specific biology of cholangiocyte injury and regeneration remains underexplored. Recent evidence highlights purinergic signaling as a key regulatory axis in the liver's response to ischemia. Upon hypoxic stress, extracellular ATP is released as a damage-associated molecular pattern (DAMP), activating pro-inflammatory P2 receptors. Enzymatic degradation of ATP by CD39 and CD73 shifts the signaling balance toward adenosine, a potent anti-inflammatory and cytoprotective molecule acting through P1 receptors (A1, A2A, A2B, A3). This review synthesizes emerging data on purinergic signaling in cholangiocyte biology, emphasizing its role in modulating inflammatory injury, cellular crosstalk, and regeneration. We discuss how A2A and A2B receptor pathways suppress immune-mediated damage and promote cholangiocyte proliferation, with downstream effects on IL-6 secretion, vascular remodeling, and bile duct survival. As biliary complications remain a major cause of graft dysfunction post-transplant, harnessing purinergic mechanisms may offer a novel therapeutic frontier in improving cholangiocyte resilience and overall transplant outcomes.